2022
DOI: 10.1590/1980-265x-tce-2021-0187
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Knowledge, Attitudes and Practices Regarding Hepatitis B: An Integrative Review

Abstract: Objective: to analyze, in the literature, the nurses' knowledge, attitudes and practices regarding Hepatitis B. Method: an integrative review, with search and selection conducted independently by peers, after electronic queries in the CINAHL, MEDLINE, SCOPUS, Web of Science, LILACS, BDENF and IBECS databases in January 2021. The sample consisted in 15 primary studies published with no time or language restrictions. Analysis and synthesis of the results were carried out in a descriptive manner. Results: lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…A review in 2022 showed that the knowledge, attitudes, and practices of nurses in relation to Hepatitis B was limited and inconsistent, that may result in increased occupational exposure, poor vaccination coverage, and high incidence of hepatitis B among nurses. [ 7 ] Another study of 4,474 nursing professionals from 292 institutions across 12 states of India found that participants had poor knowledge (19.3 ± 4.4 in pre-test) regarding viral hepatitis and its transmission which significantly ( P value <0.001) improved after a one day training (25.7 ± 3.9 in post-test). [ 8 ] The study also assessed the impact of the training, which revealed that on a regular basis 82.0% of the participants initiated the use of personal protective equipment's; 97.9% adopted safe injection practices; 83% advised about HBV vaccination, and 79.8% for family screening.…”
Section: Introductionmentioning
confidence: 99%
“…A review in 2022 showed that the knowledge, attitudes, and practices of nurses in relation to Hepatitis B was limited and inconsistent, that may result in increased occupational exposure, poor vaccination coverage, and high incidence of hepatitis B among nurses. [ 7 ] Another study of 4,474 nursing professionals from 292 institutions across 12 states of India found that participants had poor knowledge (19.3 ± 4.4 in pre-test) regarding viral hepatitis and its transmission which significantly ( P value <0.001) improved after a one day training (25.7 ± 3.9 in post-test). [ 8 ] The study also assessed the impact of the training, which revealed that on a regular basis 82.0% of the participants initiated the use of personal protective equipment's; 97.9% adopted safe injection practices; 83% advised about HBV vaccination, and 79.8% for family screening.…”
Section: Introductionmentioning
confidence: 99%